INTEGRATION OF LINGUISTIC AND PSYCHOLINGUISTIC MECHANISMS: A COGNITIVE NEUROLINGUISTIC INTERPRETATION OF THE TRANSLATION PROCESS - Mukhammedova Mokhinur Bakberganovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Abstract: This thesis explores translation as a multidimensional phenomenon that emerges from the integration of linguistic, psycholinguistic, and neurolinguistic mechanisms. The study aims to interpret the translation process through a cognitive-neurolinguistic lens, emphasizing the interaction between language, thought, and brain functions. It examines how perception, semantic processing, memory activation, attention management, and the reproduction of meaning in another language are coordinated in the translator’s cognitive system. The role of short-term and long-term memory, semantic activation, and neural specialization (including the Broca and Wernicke areas) is analyzed in connection with translation competence. Furthermore, the research discusses the distinction between human and machine translation from a neurocognitive perspective, highlighting the creative and culturally adaptive nature of human cognition.